Black rice bran (oryza sativa l. indica) extract cream prevented the increase of dermal matrix metalloproteinase-1 and dermal collagen reduction of male Wistar rats (rattus norvegicus) exposed to ultraviolet-B rays - Astried Haryanto; Wimpie Pangkahila; Anak Agung Gde Putra Wiraguna (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2020)
Introduction: The radiation of UV B rays exposure is capable of inducting free radicals to the skin, damaging the dermal collagen and stimulating skin aging. Photoaging prevention may be conducted by utilizing antioxidant and one of the good sources of antioxidant is black rice bran. Therefore the purpose of this research was to assess the effects of topical 35% black rice bran (Oryza sativa L.indica) extract toward dermal Matrix Metalloproteinase-1 (MMP-1) and dermal collagen in male Wistar rats (Rattus norvegicus). Method: A post-test only control group design was conducted using 36 male Wistar rats divided into 2 groups (treatment and control). Both groups were exposed to UV-B rays 3 times a week for 4 weeks but the treatment group received 35% black rice bran extract cream twice a day. The control group was only treated by base cream. Histopathological examination was used to assess MMP-1 expression while Picro Sirius Red staining was used to assess dermal collagen on the rat’s skin. Result: Comparative statistical analysis results for both groups revealed that MMP-1 expression in treatment group was significantly lower than control group (30.94±4.22% vs. 9.57±2.76%; p<0.001). Meanwhile, collagen density was significantly higher in treatment group (83.59±2.84% vs. 58.40±2.69%). Conclusion: Topical application of 35% black rice bran extract cream prevented the increase of MMP-1 expression and dermal collagen reduction. Further study is needed to validate these findings.